Testing anti‐HIV activity of antiretroviral agents in vitro using flow cytometry analysis of CEM‐GFP cells infected with transfection‐derived HIV‐1 NL4‐3. Issue 6 (9th November 2015) - Frezza, Caterina; Grelli, Sandro; Federico, Maurizio; Marino‐Merlo, Francesca; Mastino, Antonio; Macchi, Beatrice
Abstract : An assay, specifically optimized to evaluate the anti‐HIV activity of antiretrovirals by flow cytometry analysis, is described. As widely used anti‐HIV agents, zidovudine (AZT), abacavir (ABC), 2′, 3′‐dideoxyinosine (DDI), lamivudine (3TC), nevirapine (NVP), and efavirenz (EFV), and as drugs of recent approval raltegravir (RAL), etravirine (ETR), and rilpivirine (RPV), were utilized as reference drugs. HIV‐1 NL4‐3 virus was prepared by transfection of HEK293T cells with purified plasmid DNA and quantified by p24 antigen‐capture assay. For infection, CEM‐GFP cells were exposed to vehicle or to several concentrations of the drugs for 2 hr at 37°C before HIV‐1 NL4‐3 was added to each sample. The adsorption was prolonged for 3 hr at 37°C. After 72 hr of incubation, HIV‐induced GFP expression in infected CEM‐GFP cells was assessed by flow cytometry analysis and expressed as % positive cells. For comparison, p24 production in supernatants was assessed by a commercial ELISA kit. On the basis of IC50 values, the anti‐HIV activity, as assayed by this method, was EFV > 3TC > AZT > NVP > DDI > ABC and ETR > RPV > RAL. The comparison between the IC50 values calculated through flow cytometry and p24 production revealed overlapping results, showing that the optimized protocol of CEM‐GFP infection with HIV NL4‐3 is a suitable method to perform quantitative, rapid and low‐expensive screening tests to evaluate the in vitro effect of new candidate anti‐HIV drugs. J. Med. Virol. 88:979–986, 2016 . © 2015 Wiley Periodicals, Inc.